2018
DOI: 10.4274/jus.2143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Complications of Holmium Laser and Pneumatic Lithotripters Used in the Ureterorenoscopic Treatment of Proximal Ureter Stones, a Multi-Center Study of Society of Urological Surgery Aegean Study Group

Abstract: What's known on the subject? and What does the study add?Objective: The aim of this study is to compare the efficacy and complications of holmium laser and pneumatic lithotripsy used in the ureterorenoscopic treatment of proximal ureteral stones. Materials and Methods: Data of 638 patients, who underwent ureterorenoscopy (URS) due to proximal ureteral stones in different centers, were obtained from patient files. The patients were divided into two groups according to the type of lithotripter used: group 1; las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…In the literature, the success rate of LL in proximal ureteral stones ranges between 81.8% and 96% [26][27][28][29][30]. In this study, we found that LL was superior to PL in the treatment of proximal ureteral stones, consistent with the literature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the literature, the success rate of LL in proximal ureteral stones ranges between 81.8% and 96% [26][27][28][29][30]. In this study, we found that LL was superior to PL in the treatment of proximal ureteral stones, consistent with the literature.…”
Section: Discussionsupporting
confidence: 89%
“…According to the literature, the reason for the high overall success rate in our study is that the number of patients in the mid and distal ureteral stones was considerably higher than the number of patients in the proximal ureter, and the stone migration rate is low in stones at this level. The success rate of PL in proximal ureteral stones varies between 75% and 90.5% in the literature [5,19,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we widen the indications of DJ stenting, so we fix it even when the mucosal injury is not extensive to allow ordered ureteral healing and avoid stricture development. DJ stenting was significantly less in the combined relative to laser group, 51.1% versus 64.4%, respectively, which matches the finding of Irer et al who reported that DJ stenting was significantly lower in their pneumatic group versus laser [13]. The goal of lithotripsy process is to produce small stone chunks that can be passed out spontaneously or easily retrieved, this goal is still easily achieved in both groups, and the lithotripsy time and operative time (mean ± SD) were nearly the same in laser and combined groups (15.5 ± 12.2 vs. 17.3 ±7.2) and (40.7 ± 26.3 vs. 43.2 ± 21.6) minutes, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…EAU recommended Ho:YAG laser lithotripsy as a gold standard procedure for ureteroscopic intracorporeal lithotripsy because of its efficiency to fragment all stone types, ablative effect and stone dusting [9]. However, pneumatic energy is stronger and cheaper than Ho:YAG laser with minimal tissue trauma [10][11][12][13]. These different lithotripter mechanisms (mechanical vs. photothermal) affect the stone-free and upward migration.…”
Section: Discussionmentioning
confidence: 99%
“…Sophistication of medical instrumentation and miniaturization of scopes has changed urological practice [20,21] . Although several energy sources are available but pneumatic and laser energy are favored because of their high SFRs (>90%) and lower complications rates [22,23] . Laser energy is now more favored to treat ureteric stones.…”
Section: Discussionmentioning
confidence: 99%